Renewal out of the spirit of the own tradition? On continuity and change of nation-specific patterns of the cognitive and social organisation of educational studies - Keiner, Edwin; Schriewer , Jürgen (Swiss Journal of Educational Research, 2000)
The institutionalisation of Education as an academic field of study just as of the social sciences more generally has occurred/taken place, since the late 19th century, under the conditions of different nation-states, in the context of divergent academic institutions, and in connection with varying academic cultures. The resulting discipline formation patterns have become the subject of analyses carried through by the recent history and sociology of the sciences. Analyses of this kind have come to distinguish between the model of «comprehensive social science» (as represented, e.g., by the Durkheimian programme of sociology in France), of «formalised disciplinary discourses» (as particularly realised in German universities), and of «pragmatically specialising professions» (as observable in U.S. developments). The article takes up such models und investigates the issues of continuity and change of nation-specific patterns of the cognitive and social organisation of educational studies up to the present time, drawing mainly on citation analyses of German, French and (Anglo-)American education journals and encyclopedias.